Dissenting Opinions and Rights Protection in the European Court: A Reply to Laurence Helfer and Erik Voeten. (22nd November 2021) - Stone Sweet, Alec; Sandholtz, Wayne; Andenas, Mads
Abstract: In their article 'Walking Back Human Rights in Europe?', Helfer and Voeten (hereinafter 'H-V') argue that a series of High Level Conferences (2012–2018), specifically Brighton (2012), dramatically altered the style of the European Court of Human Rights' (ECtHR) decision-making. The Grand Chamber began to adopt judgments which, in turn, provoked an unprecedented wave of 'Walking-Back Dissents'. Such dissents are separate opinions that, in effect, accuse the majority of a Grand Chamber of 'tacitly overturn[ing] prior rulings or settled doctrine in favour of national governments' (H-V, p. 823). In an expansive conclusion, H-V suggest that the ECtHR has also generated a rising number of 'Walking-Back Judgments', which lower standards of rights protection. We reject H-V's major claims on the empirical evidence. The outcomes of Brighton and subsequent conferences did not pose a credible threat to the Court, and could not have induced it to 'walk back' rights protection. We also closely examined two sets of Walking-Back Dissents identified by H-V, focusing on judgments that would be 'most likely to fit' H-V's 'expectations'. We found that fewer than one in four judgments analysed actually contained a Walking-Back Dissent. And we identified only one plausible Walking-Back Judgment. We are confident that H-V's results are inaccurate and cannot be reproduced by external analysts. We conclude by noting factors that H-V do not consider, but that are crucial to understanding the ECtHR's decision-making. In appendices, posted online, we summarize and give reasons for our coding decisions.